KONSEP KINERJA DALAM STUDI ORGANISASI PUBLIK - Ishak, Deding; Maolani, Dedeng Yusuf; Engkus, Engkus (JISPO Jurnal Ilmu Sosial dan Ilmu Politik, 2017)
Conscientiousness initiative, interpersonal support, and organizational support are still the prime problem in the performance achieve process. It’s thought to have been caused by individual performance not done optimally yet.The aim of the research for understanding the good organizational performance that first contribution from individual performance in the organization. At the least, responsibility of the individual of the organization. The responsibility internally in the organization and for public responsibility externally.The methodology use are qualitative, the first to library study, and study of factual comparative complately, with central issue in the beaucracy, especially in Indonesia.The study of performance has been done since 1913 by Munstenberg in the conclusion that individual performance is the central role in a organization. Responding the society dynamics and global era. Conclusion the writer that study of performance have been relevantly until now and important to reasearch continously.